Promoting differentiated energy savings: Analysis of the psychological motivation of households with different energy consumption levels. (1st March 2021) - Mi, Lingyun; Xu, Ting; Sun, Yuhuan; Yang, Hang; Wang, Bangjun; Gan, Xiaoli; Qiao, Lijie
Abstract: Increasing attention has been paid to household energy savings in reducing carbon emissions. However, previous studies have rarely distinguished different energy consumption levels (ECLs) in investigations of energy-saving psychological motivation. To promote the energy-saving of households with different ECLs, a two-stage study was conducted in Xuzhou, Jiangsu Province, China. First, we clustered the annual electricity consumption of all households in the sample communities (4, 422) and classified the household ECLs into three levels: high, medium, and low. Then, based on the theory of planned behavior, we investigated and analyzed the differences in the psychological factors affecting actual household electricity consumption of the three household types with different ECLs. Results showed that the actual electricity consumption of the three levels generated by clustering was significantly lower than the corresponding threshold values of local tiered electricity pricing. In addition, significant differences existed in energy conservation psychology among the three types of ECLs. These findings provide new perspectives and opportunities for policymakers to differentiate energy-saving incentive strategies and promote the fairness of emission reduction responsibilities. Highlights: A two-stage study was carried out to promote differentiated energy savings. ECLs were classified by household electricity data clustering. The theory of planned behavior was applied to psychological motivation stratified analysis. Psychological motivations affecting household electricity use varied with ECLs. Differentiated policy implications to promote energy conservation are proposed.